Climate-stressed crop mycobiomes as pre-harvest sentinels of human mycotoxin exposure: an AI-enabled One Health framework linking dysbiosis, exposomics, and toxicopathology - Sayandeep K. Das; Prithviraj Karak; Prachi Parvatikar (Frontiers in Systems Biology, 2026)
Climate change is altering the conditions under which crop-associated fungi colonize plants and produce mycotoxins. Current control relies on both pre-harvest management and post-harvest testing; however, field-level fungal-community changes are rarely used to guide where and when testing should be intensified. This Review critically compares evidence linking weather and crop stress, fungal-community composition, toxigenic strain activity, contamination during harvest and storage, human biomarkers, and organ-specific effects. On this basis, we propose the Crop Mycobiome-Exposome-Toxicopathology Axis as a testable One Health model, not as a validated diagnostic pathway. Heat, drought, rainfall sequence, insect injury, drying delay, and storage moisture can alter host susceptibility and fungal competition, but their effects differ by crop, fungal guild, and stage of the food chain. Evidence is strongest for climate-linked aflatoxin modelling, maize mycobiome-toxin associations, atoxigenic Aspergillus biocontrol, biomonitoring feasibility, and aflatoxin-related hepatocarcinogenesis. Direct field-to-human datasets remain scarce. We therefore conclude that crop mycobiome measurements may complement, but cannot replace, toxin assays and post-harvest controls. The priority is prospective, paired field-food-human research that tests whether mycobiome indicators improve prediction and intervention timing beyond weather and commodity testing alone.